The Relationship of Knowledge with The Practice of Postpartum Gymnastics in Postpartum Mothers in PMB Rahmawati Welahan Jepara - Ainia Fatimatuzzahro’; Irawati Indrianingrum; Ana Zumrotun Nisak (Advances in Healthcare Research, 2026)
Purpose: This study aimed to determine the relationship between knowledge and the practice of postpartum gymnastics among postpartum mothers at PMB Rahmawati Welahan Jepara. It was hypothesized that greater maternal knowledge would be associated with more frequent postpartum gymnastics practice. Research Method: This study used a quantitative analytical design with a pre-experimental one-group pretest-posttest approach. The sample consisted of 30 postpartum mothers selected using accidental sampling. Data were collected using a multiple-choice questionnaire to measure knowledge and a Likert-scale questionnaire to assess postpartum gymnastics practice. Univariate analysis was used to describe respondent characteristics and variable distributions, while bivariate analysis used Somers'd test. Results and Discussion: Before education, most respondents had poor knowledge (76.7%), but after education, most had good knowledge (83.3%). In practice, 76.7% of mothers performed postpartum gymnastics in the good category. Statistical analysis showed a significant positive relationship between knowledge and practice (p = 0.020; r = 0.696), indicating that mothers with better knowledge tended to practice postpartum gymnastics more appropriately. Implications: These findings highlight the importance of structured, continuous health education to improve maternal knowledge and support healthy postpartum recovery behaviors. Further studies should explore other influencing factors such as family support, motivation, and cultural beliefs.